Conception of Quality of University Hospitals Employees and the Importance of Quality Work Communication: A Practical Example - Çolaklar, Huriye; Bozkurt Demirdağ, Fatma (Information World, 2013)
In this study, we emphasize that the public institution employees are also that should be aware that problems can be solved by means of communication for the purpose of appreciating the quality of work and making it effective. The survey was used as a method of data collection and that survey was conducted on office managers and academic staff. The survey sheets were sent out to 205 people and 173 of them were returned. Four of the survey sheets weren’t evaluated as they were either incomplete or wrongly-filled. 29 out of 173 employees were managers. As a result of the survey with the strengths of the institution in terms of quality, we can conclude that “the communication and decision of mechanisms” was identified as “the least important” with 23% according to managers. “The motivating mood of the organization” was identified as “important” with 33% according to academic staff. Among all the difficulties in quality management, “the high management of management approach” with 39% and “the lack of communication in the institution” were identified as “the least important” with 38% according to managers, whereas “the lack of communication” was “little important” with 23% amongst academic staff. In conclusion, it is determined that employees find understanding the quality service and customer satisfaction is very important and the contribution of communication has little importance in establishing a quality management system. However the lack of communication in the institution and disagreements between the departments affect effectiveness of quality managing system and development of the conscious of quality in a negative way.
Keywords: Quality management; Communication; University hospitals